Shaping a Collective Identity through Self-Representation: Early Suffrage Autobiographies and the Militant Experience - Chloé Clément (Cahiers Victoriens et Edouardiens)
This essay aims to demonstrate the interdependent relationship between self-representation and collective identity in the militant suffrage campaign by focusing on two early suffragette autobiographies, Emmeline Pankhurst’s My Own Story and Constance Lytton’s Prisons and Prisoners. Both published in 1914, these autobiographies establish a common militant experience in the suffrage campaign of the Women’s Social and Political Union (WSPU) through the personal accounts and testimonies of their authors. Transformed into political tools, these autobiographies blur the limits between private experience and public sharing. Constance Lytton and Emmeline Pankhurst indeed share how personal narratives fit with political objectives and manifest a collective purpose: that of promoting and legitimizing the militant suffrage campaign. Studying Lytton’s and Pankhurst’s militant experiences portrayed in their autobiographies, observing the reception of these personal writings, or identifying the way the militant spirit is built through reproductions of personal experiences will therefore demonstrate how self-representation shaped and supported the WSPU’s collective identity. The reproduction of imprisonments, hunger strikes or other militant actions assert defining characteristics of militant experience and contribute to emphasise a collective identity built upon self-sacrifice, devotion, and martyrdom. While these autobiographies demonstrate how the self-representation of individual experiences had a collective purpose and influence over a community, they also describe how notions of self-representation and collective identity are reciprocal. Lytton’s autobiography, for instance, represents her journey as a suffragette who sought to fit in by adapting her militancy to the movement’s collective identity. Therefore, My Own Story and Prisons and Prisoners not only act as platforms to share one’s story of the suffrage movement but also demonstrate the political power of personal experiences in creating a spirituality that included personal militant experiences into a greater collective environment. These early suffrage autobiographies thus become essential tools in questioning and understanding the relationship between personal and collective, private and public.